Reconstructing the phylogeny of the hornless rhinoceros Aceratheriinae - Lu, Xiao-Kang; Deng, Tao; Pandolfi, Luca (Frontiers in Ecology and Evolution, 2023)
This study presents the first phylogenetic analysis focused on the subfamily Aceratheriinae to date, with 392 characters (361 parsimony-informative characters) coded from 50 taxa at the species level. We added 80 newly defined and 33 revised characteristics to an existing matrix, covering features of the skull, teeth, and postcranial bones. Based on the results of ordered and unordered analyses, combined with a diagnosis in accordance with traditional morphological taxonomy, we revised the diagnosis of Aceratheriinae and reconstructed the phylogeny of Aceratheriinae. The tribe Teleoceratini, as well as the tribe Aceratheriini, was reclassified within Aceratheriinae; however, the traditionally established contents of each tribe were changed somewhat. Aceratheriinae underwent evolutionary adaptation several times during the early stages of its evolution, and several genera are herein reconstructed as early-diverging taxa, such as Floridaceras, Chilotheridium, and Plesiaceratherium. Turkanatherium and Protaceratherium are excluded from Aceratheriinae in this study. We suggest another two subclades of Aceratheriinae, containing Hoploaceratherium and Aprotodon, respectively. Aceratheriini and Teleoceratini are redefined as two highly specialized groups of Aceratheriinae.